Analisis Pengelola Barang Milik Daerah Pada Laporan Keuangan Pemerintah Kabupaten Kotawaringin Timur - Mambang Mambang; Fadli Fadli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This research is agreed to explore and analyze the management of regional goods in the financial report of the East Kotawarwant regency. This is to find out how the Kotim regional government has received an unexempted WTP or reasonable opinion from 2013 to 2018. The type of research used is a type of qualitative research, namely; Describe aspects related to the research object in depth. The location of this research is conducted on Regional device Unit (SKPD) in the government of East Kotawarwants regency. The results of this research show the management of assets/property goods carried out by the area of assets on the body of financial management and regional assets as the manager's assistant has done with the maximum and according to the system and procedure cycle Management of regional goods as stipulated in PERMENDAGRI number 19 year 2016 about the guidelines for management of local goods, and East Kotawaringin PERDA number 4 year 2010, but not all carried out with maximum, especially To the regional head policy on the HR management of goods. Some obstacles or inhibitory factors encountered in the implementation of the management cycle of regional property is the HR factor because of the need for knowledge and understanding of human resources in asset management.